No genetic causal association between Alzheimer’s disease and osteoporosis: A bidirectional two-sample Mendelian randomization study - Hu, Hongxin; Mei, Jian; Cai, Yuanqing; Ding, Haiqi; Niu, Susheng; Zhang, Wenming; Fang, Xinyu (Frontiers in Aging Neuroscience, 2023)
Objective: Many observational studies have found an association between Alzheimer's disease (AD) and osteoporosis. However, it is unclear whether there is causal genetic between osteoporosis and AD. Methods: A two-sample Mendelian randomization (MR) study was used to investigate whether there is a causal relationship between osteoporosis and AD. Genes for osteoporosis and AD were obtained from published the genome-wide statistics (GWAS). Single nucleotide polymorphisms (SNPs) with significant genome-wide differences (P< 5×10-8) and independent (r2< 0.01) were selected, and SNPs with F≥10 were further analyzed. Inverse variance weighted (IVW) was used to assess causality, and the results were reported as odds ratios (ORs). Subsequently, heterogeneity was tested using Cochran's Q test, pleiotropy was tested using the MR-Egger intercept, and sensitivity analysis was performed using leave-one-out sensitivity rates to assess the robustness of the results. Results: Using the IVW method, MR Egger method, and median-weighted method, we found that the results showed no significant causal effect of osteoporosis at different sites and at different ages on AD, regardless of the removal of potentially pleiotropic SNPs. Conversely the results were similar. These results were confirmed to be reliable and stable by sensitivity analysis. Conclusion: This study found that there is no bidirectional causal relationship between osteoporosis and AD. However, they share similar pathogenesis and pathways.